107k views
0 votes
X + 3y = 7 x + y = 3 elimination

User Megharaj
by
6.0k points

2 Answers

4 votes

Answer:

x + 3y = 3

7x + y = 3

*Multiply both sides

-7x - 21y = -21

7x + y = 3

*eliminate one variable by adding the equations

-20y = -18

*Divide both sides

y = 9/10

*substitude the value of y

x + 3 x 9/10 = 3

*slove the equation

x = 3/10

*A possible solution is

(x , y) = (3/10 , 9/10)

*check the solution

3/10 + 3 x 3/10 = 7 x 3/10 + 9/10 =3

*simplify

3 = 3 =3

*The ordered pair is a solution

( x , y ) = ( 3/10 , 9/10 )

User Jose Paez
by
5.9k points
3 votes

Answer:

Explanation:

// Solve equation [2] for the variable y

[2] y = -x + 3

// Plug this in for variable y in equation [1]

[1] x - 3•(-x +3) = 7

[1] 4x = 16

// Solve equation [1] for the variable x

[1] 4x = 16

[1] x = 4

// By now we know this much :

x = 4

y = -x+3

// Use the x value to solve for y

y = -(4)+3 = -1

Solution :

{x,y} = {4,-1}

User Amethi
by
5.9k points